Peran Supervisi Klinis Dalam Meningkatkan Kompetensi Pedagogik Guru Sekolah Dasar: Peran Supervisi Klinis Dalam Meningkatkan Kompetensi Pedagogik Guru Sekolah Dasar - Supyan Sauri; Rohman Sidik; Ita Rosita; Euis Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to thoroughly analyze the role of clinical supervision in improving the pedagogical competence of teachers at SDN Margaasih, Bandung Regency. Using a qualitative approach and a case study design, data were collected through direct observation of the learning process, in-depth interviews with teachers and the principal, as well as document review related to the implementation of supervision. The findings indicate that clinical supervision contributes significantly to enhancing the quality of learning through a structured coaching process, consisting of pre-observation, classroom observation, and post-observation stages. In the pre-observation stage, supervisors assist teachers in formulating clearer learning objectives and designing instructional materials that align with students’ needs. The observation stage enables supervisors to objectively identify the strengths and weaknesses of teaching practices. Meanwhile, in the post-observation stage, teachers receive constructive, reflective, and solution-oriented feedback that encourages improvements in didactic skills, classroom management, the use of varied instructional models and media, and teachers’ self-reflection abilities. This study affirms that clinical supervision is an effective professional development strategy for strengthening teachers’ pedagogical competence and positively impacts the quality of teaching and learning outcomes in elementary schools.